NATO and Putin's Russia: Seeking to balance divergence and convergence. Issue 5 (19th October 2016) - Kfir, Isaac
ABSTRACT: This article argues that NATO is unable to challenge any of President Putin's expansive policies for two key reasons: First, Europe and the United States have conflicting views on what events qualify as key security threats (different threat perceptions). Infused within this paradigm is a nascent European Union strategic culture that views threats differently from the U.S. This in turn undermines NATO, as the Europeans argue for largely nonmilitary or more peacekeeping-oriented approaches to respond to threats that are quintessentially multilateral. Second, even though there are major differences between the NATO states and Russia, the two most pressing issues before the Atlantic Alliance are Iran and Syria. The NATO states know that a resolution to the Syrian civil war or to Iran's nuclear program is unlikely without the support of Moscow, which limits their ability to effectively challenge Russia. This article concludes with a call for NATO to focus on identifying a new agenda for the Atlantic Alliance, one that is more human-security oriented, as it addresses the root causes of instability in and around the Eurozone.